2000
DOI: 10.1016/s0092-8674(00)00088-x
|View full text |Cite
|
Sign up to set email alerts
|

The Polar T1 Interface Is Linked to Conformational Changes that Open the Voltage-Gated Potassium Channel

Abstract: Kv voltage-gated potassium channels share a cytoplasmic assembly domain, T1. Recent mutagenesis of two T1 C-terminal loop residues implicates T1 in channel gating. However, structural alterations of these mutants leave open the question concerning direct involvement of T1 in gating. We find in mammalian Kv1.2 that gating depends critically on residues at complementary T1 surfaces in an unusually polar interface. An isosteric mutation in this interface causes surprisingly little structural alteration while stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
178
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(194 citation statements)
references
References 60 publications
(4 reference statements)
11
178
1
Order By: Relevance
“…How can the oligomerization͞trafficking competence of TRPM6 be affected by mutation of S141, which is located far away from the putative transmembrane segment? It is tempting to speculate that the TRPM N terminus serves a similar role for the multimerization of ion channel subunits as the N-terminal T1 domains in voltage-gated K ϩ channels (24).…”
Section: Discussionmentioning
confidence: 99%
“…How can the oligomerization͞trafficking competence of TRPM6 be affected by mutation of S141, which is located far away from the putative transmembrane segment? It is tempting to speculate that the TRPM N terminus serves a similar role for the multimerization of ion channel subunits as the N-terminal T1 domains in voltage-gated K ϩ channels (24).…”
Section: Discussionmentioning
confidence: 99%
“…This multipurpose domain, which also serves as a docking station for intracellular auxiliary proteins (3,5,(33)(34)(35) and has been implicated in channel trafficking (36) and gating (14,15,37,38), acts at early stages of assembly when the peptide chains are still attached to ribosomes (39). The function of the T1 domain in the assembly process is 2-fold, providing stabilizing interactions for some, and prohibiting the interaction of other subunits.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the voltage-gated K + channel (Kv), electrophysiological studies with toxin blockers showed the functional unit to be a tetramer 11 , a finding that was confirmed by X-ray crystallography [12][13][14][15] . Assembly of the four subunits into the tetrameric channel forms the permeation pathway in the centre.…”
mentioning
confidence: 89%